PARAMETRIC MANDIBLE RECONSTRUCTION PLATE - Giddy, Brett; van der Merwe, Johan (The South African Journal of Industrial Engineering, 2020)
This study investigated the feasibility of a parametric mandible reconstruction plate in order to reduce surgical lead time, improve fit, and reduce residual stresses. The parametric plates were generated on the basis of simulated cephalometric measurements. A finite element analysis and a reconstruction plate/mandible fit test were performed on several combinations to determine whether the parametric plate provided a suitable alternative to conventional reconstruction plates in terms of fit and structural performance. The results indicated that the parametric plate is structurally superior to a conventional plate. The comparison test indicated that the parametric plate provides a reasonable approximation of mandible geometry.